2013
DOI: 10.1016/j.jmmm.2012.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Electron paramagnetic resonance study of (La0.33Sm0.67)0.67Sr0.33−Ba MnO3 (x<0.1): Griffiths phase

Abstract: a b s t r a c tManganite compounds (La 0.33 Sm 0.67 ) 0.67 Sr 0.33 À x Ba x MnO 3 with light Ba doping (x ¼ 0.01-0.09) have been investigated by electron paramagnetic resonance over the temperature range 110-450 K. It was found that the EPR linewidth behavior changed drastically in samples with these low Ba concentrations. For all the samples there was observed coexistence of paramagnetic and ferromagnetic phases below the phase-transition (Curie) temperature. EPR signals characteristic of a Griffiths phase we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 24 publications
1
2
0
1
Order By: Relevance
“…The presence of the extra line at the PM region can give the evidence for the existence of the additional magnetic phase in this material. A similar character of the EMR spectra has been reported by other authors for manganites [16][17][18][19], where this phenomena were assigned to Griffiths phase [22], and for amorphous Fe-rich Fe 100−x Zr x alloys [23], where the explanation of the resonance above T C was based on the model of infinite ferromagnetic matrix and finite spin clusters embedded in, but isolated (in sense of ferromagnetic interaction) from, this infinite cluster. In our case, however, the behavior of the FM signal is a little different from that reported in the above cited papers.…”
Section: Resultssupporting
confidence: 82%
“…The presence of the extra line at the PM region can give the evidence for the existence of the additional magnetic phase in this material. A similar character of the EMR spectra has been reported by other authors for manganites [16][17][18][19], where this phenomena were assigned to Griffiths phase [22], and for amorphous Fe-rich Fe 100−x Zr x alloys [23], where the explanation of the resonance above T C was based on the model of infinite ferromagnetic matrix and finite spin clusters embedded in, but isolated (in sense of ferromagnetic interaction) from, this infinite cluster. In our case, however, the behavior of the FM signal is a little different from that reported in the above cited papers.…”
Section: Resultssupporting
confidence: 82%
“…A nature of the mixed phase is different from the so called Griffiths phase since the manganites studied do not exhibit the downturn deviation in magnetic susceptibility nor inverse intensity of signal [34]. There is also no indication of Griffiths phase in resonance signal registered for manganites studied [35]. In contrast to the Griffiths phase containing relatively large ferromagnetic clusters, the observed mixed phase seems to be built of small clusters.…”
Section:  mentioning
confidence: 70%
“…3c) which can be attributed to the disorder [12]. Such observation can be the signature of Griffiths phase [14]. When investigating the system (La 1/3 Sm 2/3 ) 2/3 Sr x Ba 0.33−x MnO 3 (x = 0, 0.1, 0.2 and 0.33), ESR study have shown that the samples with x = 0.1 and 0.2 were characterized by the presence of Griffiths phase induced by the disorder generated by increasing barium content [9].…”
Section: Resultsmentioning
confidence: 99%